PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PANEN DI PT. DEWATA SAWIT NUSANTARA - Syahrul B; Jamaluddin; M. Atta Bary; Sri Ngapiyatun; Rusli Anwar (Politeknik Pertanian Negeri Samarinda, 2019)
This study is motivated by how the work environment influences the performance of harvest employees with the limitation of problems in work environment activities that will affect the performance of harvest employees on oil palm plantations at PT. Dewata Sawit Nusantara. It should be understood that the expected performance of an employee is not easy because it is influenced by various compensation factors, motivation, work environment and many other factors. This study aims to determine whether the work environment influences the performance of harvest employees at PT. Dewata Sawit Nusantara. The data analysis method used was a simple linear regression statistical analysis and uses a hypothesis test to analyze the closeness of the relationship of individual variables, while testing the instrument using a validity and reliability test. Statistical test results showed that the relationship between work environment and employee performance was positive (unidirectional). Based on the results of hypothesis testing obtained a significant value of 5% then H1 was accepted or Ho was rejected. This means that the work environment influenced the performance of harvest employees at PT. Dewata Sawit Nusantara.